Albiflorin Promotes Osteoblast Differentiation and Healing of Rat Femoral Fractures Through Enhancing BMP-2/Smad and Wnt/β-Catenin Signaling - Kim, Jae-Hyun; Kim, Minsun; Hong, SooYeon; Kim, Eun-Young; Lee, Hyangsook; Jung, Hyuk-Sang; Sohn, Youngjoo (Frontiers in Pharmacology, 2021)
Fracture healing is related to osteogenic differentiation and mineralization. Recently, due to the unwanted side effects and clinical limitations of existing treatments, various natural product-based chemical studies have been actively conducted. Albiflorin is a major ingredient in Paeonia lactiflora, and this study investigated its ability to promote osteogenic differentiation and fracture healing. To demonstrate the effects of albiflorin on osteoblast differentiation and calcified nodules, alizarin red S staining and von Kossa staining were used in MC3T3-E1 cells. In addition, BMP-2/Smad and Wnt/β-catenin mechanisms known as osteoblast differentiation mechanisms were analyzed through RT-PCR and western blot. To investigate the effects of albiflorin on fracture healing, fractures were induced using a chainsaw in the femur of SD rats, and then albiflorin was intraperitoneally administered. After 1, 2, and 3 weeks, bone microstructure was analyzed using micro-CT. In addition, histological analysis was performed by staining the fractured tissue, and the expression of osteogenic markers in serum was measured. The results demonstrated that albiflorin promoted osteoblastogenesis and the expression of RUNX2 by activating BMP-2/Smad and Wnt/β-catenin signaling in MC3T3-E1 cells. In addition, albiflorin upregulated the expression of various osteogenic genes, such as ALP, OCN, BSP, OPN, and OSN. In the femur fracture model, micro-CT analysis showed that albiflorin played a positive role in the formation of callus in the early stage of fracture recovery, and histological examination proved to induce the expression of osteogenic genes in femur tissue. In addition, the expression of bone-related genes in serum was also increased. This suggests that albiflorin promotes osteogenesis, bone calcification and bone formation, thereby promoting the healing of fractures in rats.